THE USE OF THE AUTHENTIC TRIBAL DIALECT AS A BRANDING TOOL IN SOCIAL MEDIA MARKETING: TABUK REGION AS A CASE STUDY - Al-Rohili, Mohammad; Alaodini, Hind (ShodhKosh: Journal of Visual and Performing Arts, 2026)
With the rapid expansion of the use of social media as a primary marketing platform, some influencers are adopting communication methods that are closer to the audience and more expressive of their cultural identity. One such method is the use of authentic tribal dialects in the content provided by influencers, which reflects the linguistic and social particularities of local communities, especially in regions like Tabuk, which is characterized by its tribal depth and rich cultural heritage. This study aims to identify the attitudes of the study sample towards the using of Authentic Tribal Dialect as a Branding Tool Marketing by influencers in Social Media in Tabuk region and its role in Increased purchases of Saudi followers. In order to achieve this objective, a Descriptive-Analytical methodology was used, and conducted systematic random sampling to select (150) followers of a number of influencers content in the Tabuk region of Saudi Arabia. To achieve the study's objective, an electronic questionnaire was used as a tool to collect data from the study sample. Results showed a high level, with a mean of (4.278) for the perceptions of the study sample regarding the Use of the Authentic Tribal Dialect as a Branding Tool in Social Media Marketing in Tabuk region, also influencers in Tabuk employing the local dialect contributes to building a closer and more authentic connection with their audience, particularly those who value cultural identity and heritage, such as followers of social/cultural content and those who consistently follow influencers. Also, the results showed that there is a statistically significant differences between the answers of the study sample members regarding the Use of the Authentic Tribal Dialect as a Branding Tool in Social Media Marketing in Tabuk region according to the personal variable (type of favorite Content) for the Category (Social/Cultural), and variable (Number of times influencers are followed) for the Category (Daily/ continuously). The study recommends the thoughtful use of authentic local dialects, tailored to the nature of the target audience and the type of content presented, while maintaining a balance between authenticity and professionalism in the marketing discourse. Furthermore, the study highlights the need for further research in different regions and across other variables to gain a deeper understanding of the impact of cultural and linguistic factors on digital marketing.